Pengembangan Computer Aided Design(CAD) Warna Batik - Mega Inayati Rif’ah; Muh. Arif Wibisono (Forum Teknik, 2016)
One of the problem faced by Indonesian batik industry is about environment issue. This is because batik industry uses synthetic dyes on their coloring process. The use of natural dyes for batik makers deemed to be impractical and has many disadvantages, including lack of bright colors, longer process, and more expensive. Therefore, this research aims to reduce the use of synthetic dye in batik design process, by developing computer aided batik color design (CAD for batik color). This development includes a method for predicting color, methods and algorithms used in the CAD and measurement of its usability level. The results showed that the method can predict color with average error rate of 5% (< 10% tolerance error established), CAD for batik color has been able to run as the concept of batik making, and its usability average value is 3.86. Therefore, it is concluded that CAD for batik color has usability aspects and can be implemented as a design batik color tool that can be operated by its user.Keywords: batik, creative, design, CAD, color